Indeks Kinerja Sistem Jaringan Irigasi Menggunakan Aplikasi E-Paksi pada Daerah Irigasi Grojogan Kabupaten Jepara - Fadhil Muhammad, Nicko; Skriptianata Putra Pranida, Pipit; Hidayat, Fahrul (Faculty Of Engineering University 17 August 1945 Semarang, 2025)
The purpose of this study was to obtain data on irrigation assets in the Grojogan irrigation network at this time, to analyze the performance conditions of the Grojogan Irrigation Network system (very good, good, less or poor), to obtain the results of the Grojogan irrigation system performance index from the results of the performance assessment using the ePAKSI application. The results of the irrigation asset management inventory include the main building consisting of 1 dam. The carrier channel consisting of a secondary channel of 1.71 km and a tertiary channel of 2.62 km. The building on the carrier channel consisting of 5 regulatory buildings and complementary buildings (4 culverts, 2 waterfalls, 6 inlets, 1 side spillway building, and 4 bridges). The performance conditions of the irrigation system are included in the Poor Performance (J) criteria so that immediate attention and handling are needed. The overall results of the Irrigation System Performance Index (IKSI) from the performance assessment of the main irrigation system and tertiary irrigation system are 51.18% (<55%)